2007
DOI: 10.1055/s-2007-957343
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Serum Adiponectin Concentrations do not Differ between Obese and Non-obese Caucasians and are Unrelated to Insulin Sensitivity

Abstract: Reduced serum levels of adiponectin in obesity and insulin resistance seem paradoxical, since adipose tissue is the only source of adiponectin, and reports on that subject are contradictory. The aim of this study was to investigate the concentrations of adiponectin in non-obese and obese normoglycemic humans, and to determine the correlation between adiponectin and HOMA index of insulin sensitivity. Based on the WHO definition of obesity, 145 obese subjects and 49 non-obese controls (aged 20-55 years) were stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 23 publications
1
7
0
Order By: Relevance
“…The relationship between adiponectin and insulin resistance previously reported in obese or diabetic children was not apparent in a populationbased study ( Kettaneh et al, 2006 ). Owecki et al reported that circulating serum adiponectin concentrations do not diff er between obese and non-obese Caucasians and are unrelated to insulin sensitivity and the same researchers also reported no relation between serum adiponectin levels and HbA1c in obese diabetic and non-diabetic Causasians ( Owecki et al, 2007( Owecki et al, , 2008. In our assumably healthy study sample selected from normal population, though not statistically signifi cant, adiponectin levels were lower in obese compared to overweight and normal subjects.…”
Section: Discussion ▼supporting
confidence: 38%
“…The relationship between adiponectin and insulin resistance previously reported in obese or diabetic children was not apparent in a populationbased study ( Kettaneh et al, 2006 ). Owecki et al reported that circulating serum adiponectin concentrations do not diff er between obese and non-obese Caucasians and are unrelated to insulin sensitivity and the same researchers also reported no relation between serum adiponectin levels and HbA1c in obese diabetic and non-diabetic Causasians ( Owecki et al, 2007( Owecki et al, , 2008. In our assumably healthy study sample selected from normal population, though not statistically signifi cant, adiponectin levels were lower in obese compared to overweight and normal subjects.…”
Section: Discussion ▼supporting
confidence: 38%
“…The baseline significant correlation of total adiponectin, but not HMW adiponectin, to sTNFR1 and sTNFR2 is also consistent with our finding that TNF-␣ neutralization affected total adiponectin levels and not HMW adiponectin. Although many studies have demonstrated a significant role for adiponectin in obesity and insulin sensitivity (3,57), other studies have shown a lack of a relationship between total circulating adiponectin and obesity or insulin sensitivity (36). Although thiazolidinedione treatment upregulates mRNA expression and plasma concentrations of adiponectin (6,31), another insulin-sensitizing agent, metformin, does not affect adiponectin concentrations (6).…”
Section: Discussionmentioning
confidence: 99%
“…Circulating levels of adiponectin are signifi cantly lower in obese than nonobese individuals, while there is a signifi cant negative correlation between serum adiponectin levels and BMI, percent body fat, waist-to-hip ratio, and intra-abdominal fat [11] . However, not all studies are consistent with these fi ndings [13,14] . Circulating adiponectin levels have also been studied in obesityrelated disorders: in type 2 diabetes, plasma adiponectin concentrations are lower than in age-and BMI-matched individuals [15] .…”
Section: Introductionmentioning
confidence: 88%